Lateral plate number in low‐plated threespine stickleback: a study of plasticity and heritability. Issue 10 (6th April 2016) - Hansson, Truls H.; Fischer, Barbara; Mazzarella, Anna B.; Voje, Kjetil L.; Vøllestad, Leif Asbjørn
Abstract: In the threespine stickleback Gasterosteus aculeatus model system, phenotypes are often classified into three morphs according to lateral plate number. Morph identity has been shown to be largely genetically determined, but substantial within‐morph variation in plate number exists. In this study, we test whether plate number has a plastic component in response to salinity in the low‐plated morph using a split‐clutch experiment where families were split in two, one half raised in water at 0 and the other at 30 ppt salt. We find a small salinity‐induced plastic effect on plate number in an unexpected direction, opposite to what we predicted: Fish raised in freshwater on average have slightly more plates than fish raised in saltwater. Our results confirm that heritability of plate number is high. Additionally, we find that variance in plate number at the family level can be predicted from other family level traits, which might indicate that epistatic interactions play a role in creating the observed pattern of lateral plate number variation. Abstract : In this study, we estimate heritability of and plasticity in lateral plate number of the threespine stickleback, a model species in evolutionary biology. Our results indicate that plate number is highly heritable and that there is an additional small plastic component in response to salinity.